Potential of Using the Investment Capacity of a Region - Morhachov Illia V. (Problemi Ekonomiki, 2018)
The aim of the article is clarifying the content of the concept “investment potential of a region”, justifying the use of additional terms that reflect the considered essence more precisely; studying subjective and objective factors affecting the investment processes in regions. The work studies the essence of potential of using the investment capacity of a region. It is proposed to use this concept in some cases instead of the term “investment potential of the region”. The proposal is based on the lack of interpretation of the latter in economic dictionaries and various interpretations of it by researchers. It is proved that if the concept “investment potential of a region” is used to denote the maximum capabilities of a region to attract and develop investments, then it is more appropriate to use the term “potential of using the investment capacity of a region”. The investment capacity of a region is defined as the maximum amount of investment that can be made and used during a certain time period in a particular region. Mathematically, the investment capacity of a region is greater than the actual volume of investment in this region within the time period i by the amount of unused potential of the investment capacity of the region within the time period i. It is specified that the larger investment capacity of the region and the potential for its use are, the greater the likelihood of investment in this region in future periods is. The larger the level of specialization of the region in the international division of labor is, the greater its investment capacity is. Innovations also increase the investment capacity of a region, so the innovation investment infrastructure of regions is a subjective factor in increasing the potential of using their investment capacity. In the context of globalization, the assertion that global investment resources exceed the investment capacity of a region becomes relevant. Integration into the world financial market is defined as the main task of the investment infrastructure of a region, and the level of such integration as the main criterion of its quality and efficiency.